Синтагматика оніма Україна в поетичному дискурсі Тараса Шевченка - Степаненко, Микола; Stepanenko, Mykola (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано синтагматичний потенціал оніма Україна на тлі його семантико-синтаксичних відношень і формально-граматичних зв’язків у художньому контексті Тараса Шевченка. З’ясовано, зокрема, сполучувальні можливості іменника Україна на рівні валентних рамок «суб’єкт + предикат», «предикат + локативний поширювач», «предикат + об’єктний поширювач», «атрибутив + суб’єкт», «атрибутив + локативний поширювач», «атрибутив + об’єктний поширювач». The article investigates the potential syntagmatic onim Ukraine in the artistic context of Taras Shevchenko on the background of its semantic and syntactic relationships and formal grammatical relations. The possibility of a noun combinability Ukraine at the level of the valence framework «subject + predicate»,«predicate + locative distributor», «predicate + object distributor», «attribute + subject», «attribute + locative distributor», «attribute + object distributor» was characterized, in particular, lexical and semantic range of the determining and determinate components , stylistic properties of attribute modifiers were defined, in particular, the core of which are possessive adjectives and demonstrative pronouns, with sociolinguistic positions were analyzed with consideration of text opposition of «my / their», which is the basis of author’s searches of national identity, ethnic and political consolidation of Ukrainians.
Syntagmatics of Onim (Proper Name) Ukraine in Poetic Discourse of Taras Shevchenko.
Keywords: онім Україна; локативний поширювач; об’єктний поширювач; атрибутивний поширювач; диференційоване значення; дієслово-предикат; вокативна синтаксема; поетичний дискурс Тараса Шевченка; onim Ukraine; locative distributor; the distributor object; differentiated value; the verb-predicate; vocative syntax; poetic discourse of Taras Shevchenko